THE IMPACT OF NATURAL DISASTERS ON CHANGE OF TRAVEL PATTERNS AND TOURIST TYPE WHO VISITED TOURISM DESTINATION - Suwena, I Ketut; Sendra, I Made; Arismayanti, Ni Ketut (Jurnal IPTA (Industri Perjalanan Wisata), 2019)
Natural disasters affect tourist travel patterns and tourist characteristics in socio-economic aspects as well as aspects of tourist behavior. This study aims to find out and analyze changes in the pattern of travel of tourists visiting Bali after natural disasters. The research was conducted in Bali tourism destinations related to the eruption of Mount Agung natural disasters in 2017. Data analysis techniques used qualitative descriptive and Likert scale techniques by distributing questionnaires to 200 tourists. The results of the study show changes in the pattern of tourist travel with natural disasters where tourists are more selective in choosing tourist attractions in these tourism destinations. Tourists state that they are not affected by natural disasters as long as there is access to the tourism destination, but information plays an important role in providing a factual description of the current conditions of tourism destinations. The motivation of tourists visiting after natural disasters did not show a significant difference.